Integration of theoretical perspectives with the analysis of blockchain technology in Higher Education (International Journal of Scientific Research in Science and Technology, 2024)
Blockchain technology offers higher education a revolutionary opportunity by enhancing academic processes’ efficiency, security, and transparency. This paper investigates the use of blockchain technology in higher education, examining the effects it has on various parties and providing suggestions for a smooth rollout. Using theoretical frameworks like Institutional Theory and Innovation Diffusion Theory, the study explores how students, teachers, administrators, and managers view and act upon blockchain adoption. The results show that effective blockchain integration requires strong infrastructure, supportive policies, thorough professional development, and positive user experiences. Furthermore, optimizing the advantages of blockchain technology in education requires strategic planning, constant assessment, and efficient stakeholder engagement. Prioritizing these actions will help educational institutions overcome obstacles, maximize blockchain functionality, and realize the full potential of the technology. Prioritizing these steps will help educational institutions overcome obstacles, make the most of blockchain technology, and realize its full potential to transform teaching and learning in the digital age. For those involved in the future of higher education, this research has implications for both theory and practice.